A Organização do Conhecimento nas Humanidades Digitais e o Conceito de Leitura Distante de Franco Moretti - Mattos, Bruno Marques de (2019)
This research aims to analyze one of the academic fields that grow most in the study of the human sciences of the main teaching and research institutions around the world: Digital Humanities. In order to do so, we have observed the path taken by scholars and supporters in the development of this recent area of study, from the first projects, through publications and major events, to the present day. Lines of research of the Digital Humanities were also explored and analyzed, especially the Organization of Knowledge. This area of study and research has the difficult task of adapting digital technologies (with its innovative tools and methodologies) to the needs of the humanities study in analyzing large and increasing quantities of texts with speed and precision. To better exemplify how complex the task Organization of Knowledge in the Digital Humanities will be, this paper analyzes the polemical concept of reading distant from scholar in literary history Franco Moretti. Probably one of the few projects in this new area of knowledge that have brought practical and meaningful results